The Problem of the Foundation of Knowledge in Plato’s Philosophy - Valevičius, Vytautas (Problemos, 1987)
The problem of the relation between knowledge and Ideas in Plato’s philosophy is discussed in the article. Zeno’s doubling of the world into the real one and the imaginary one has prompted the problem. The search of the absolute has lead Plato to ideas which became to him the base of the invariable world. Then the problem of the possibility of knowing this world by a man has arisen. Plato has preferred the rational knowing to the sensual perception and has linked the former with the rational part of soul. According to Plato, the latter knows the world of ideas from which it has come and to which it will return by means of remembering. The theory of anamnesis was a new word in the ancient philosophy.